Modulation of Long-Term Potentiation of Cortico-Amygdala Synaptic Responses and Auditory Fear Memory by Dietary Polyunsaturated Fatty Acid - Yamada, Daisuke; Wada, Keiji; Sekiguchi, Masayuki (Frontiers in Behavioral Neuroscience, 2016)
Converging evidence suggests that an imbalance of ω3 to ω6 polyunsaturated fatty acid (PUFA) in the brain is involved in mental illnesses such as anxiety disorders. However, the underlying mechanism is unknown. We previously reported that the dietary ratio of ω3 to ω6 PUFA alters this ratio in the brain, and influences contextual fear memory. In addition to behavioral change, enhancement of cannabinoid CB1 receptor-mediated short-term synaptic plasticity and facilitation of the agonist sensitivity of CB1 receptors have been observed in excitatory synaptic responses in the basolateral nucleus of the amygdala. However, it is not known whether long-term synaptic plasticity in the amygdala is influenced by the dietary ratio of ω3 to ω6 PUFA. In the present study, we examined long-term potentiation (LTP) of optogenetically–evoked excitatory synaptic responses in synapses between the terminal of the projection from the auditory cortex and the pyramidal cells in the lateral nucleus of the amygdala. We found that LTP in this pathway was attenuated in mice fed a diet with a high ω3 to ω6 PUFA ratio (0.97), compared with mice fed a diet with a low ω3 to ω6 PUFA ratio (0.14). Furthermore, mice in the former condition showed reduced fear responses in an auditory fear conditioning test, compared with mice in the latter condition. In both electrophysiological and behavioral experiments, the effect of a diet with a high ω3 to ω6 PUFA ratio was completely blocked by treatment with a CB1 receptor antagonist. Furthermore, a significant reduction was observed in cholesterol content, but not in the level of an endogenous CB1 receptor agonist, 2-arachidonoylglycerol, in brain samples containing the amygdala. These results suggest that the balance of ω3 to ω6 PUFA has an impact on fear memory and cortico-amygdala synaptic plasticity, both in a CB1 receptor–dependent manner.